2018
DOI: 10.5114/pdia.2017.68299
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and etiological factors of onychomycosis in psoriatic patients

Abstract: IntroductionThe role of a number of inherited, acquired and environmental factors has been identified to increase the risk of onychomycosis. The literature data on psoriasis as a risk factor are contradictory. The potential relationship between these pathologies is very important as it influences the patient management.AimTo evaluate the frequency of onychomycosis and etiological factors in patients with psoriasis compared to controls.Material and methodsThe studied group (n = 2427) included 2325 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 21 publications
4
15
1
2
Order By: Relevance
“…It has been reported that psoriasis patients are more likely to develop onychomycosis than the general population [ 8 , 33 , 34 ]. Nevertheless, considering that both onychomycosis and nail psoriasis usually present with similar clinical features leading to difficult discrimination and ambiguous results, some reports indicate no differences in prevalence rates between psoriasis and non-psoriasis patients with clinical nail abnormalities [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that psoriasis patients are more likely to develop onychomycosis than the general population [ 8 , 33 , 34 ]. Nevertheless, considering that both onychomycosis and nail psoriasis usually present with similar clinical features leading to difficult discrimination and ambiguous results, some reports indicate no differences in prevalence rates between psoriasis and non-psoriasis patients with clinical nail abnormalities [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies conducted to estimate the prevalence of onychomycosis in psoriatic patient provide ambiguous results. Some authors indicate that onychomycosis affects up to 79% of psoriatic patients, and the others show a low incidence of onychomycosis (15%) in this group …”
Section: Introductionmentioning
confidence: 98%
“…Pits was the most common finding in our study while others have reported ridging and pitting to be the most common [25] . It can readily be appreciated that ridging and pitting themselves contribute towards roughening of nail plate [26] . Pitting of nail plate in psoriasis is due to a defective formation of nail plate in the proximal part of nail matrix.…”
Section: Discussionmentioning
confidence: 99%